HUBUNGAN PERSEPSI ANAK TENTANG FASILITAS PERPUSTAKAAN SEKOLAH DENGAN MINAT MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DI TK ANNAMIROH 1 KOTA PEKANBARU - Anisa Zulfi; Zulkifli N '; Daviq Chairilsyah Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims 1) To determine the child's perception of school library facilities in kindergarten Annamiroh 1 Pekanbaru. 2) To determine interest in reading the beginning of children aged 5-6 years in kindergarten Annamiroh 1 Pekanbaru. 3) To determine the relationship of the child's perception of school library facilities with reading interests starters% -6 Year olds in kindergarten Annamiroh 1 Pekanbaru. The method used in this research is the correlation method. The population of this research are 52 people in kindergarten Annamiroh 1 Pekanbaru. To find samples of the study, researchers used a technique saturated samples. Saturated sample is taking the entire population for the research sample. Thus the samples used in this study amounted to 52 children. The data collection techniques used is by interview. The study hypothesis is There is a significant relationship of the child's perception of school library facilities with reading interests permulan 5-6 years old children in kindergarten Annamiroh 1 Pekanbaru. Based on the results, it can be concluded there is a strong relationship between children's perception about the school library facilities with reading interests starters 5-6 years old children in kindergarten Annamiroh 1 Pekanbaru coofesien value of 0.6333. That is, the better the child's perception about the school library facilities Early reading interests of children in kindergarten Annamiroh 1 Pekanbaru City will also increase. Keywords: Library facilities, Early reading interests.